Strategies to Improve Quality and Yield of Pyrolysis Bio-oils - Paola Brachi; Renata Migliaccio; Elvis T. Ganda; Massimo Urciuolo; Giovanna Ruoppolo; Antonio Coppola; Fabrizio Scala; Piero Salatino (Chemical Engineering Transactions, 2022)
Crude bio-oil obtained from fast pyrolysis of biomass and wastes is typically characterised by the presence of high levels of oxygenated compounds, which are mainly responsible for its unfavourable characteristics (e.g., low heating value, high acidity, and poor storage stability). In order to overcome this drawback and favourably produce drop-in fuels, the fast pyrolysis of olive stone (OS), has been studied by giving particular attention to the exploration of operating conditions (i.e. pyrolysis temperature) and strategies (i.e. catalytic pyrolysis and co-pyrolysis) suitable to promote efficient de-oxygenation of bio-oils and improve the quality of the product streams. Steady state fast pyrolysis tests were performed in a bench scale fluidized bed reactor (gas residence time ~1s). Pyrolysis tests were carried out at 500 °C and 600 °C by using either inert sand or ?-alumina catalyst as bed material. Outcomes from the non-catalytic and the catalytic co-pyrolysis of low-density polyethylene (LDPE) and OS (plastic-to-biomass ratio of 20/80) at two different temperatures (500 and 600 °C) are also presented. Preliminary findings highlight that the co-processing of LDPE and OS under non-catalytic conditions stands out for the formation of long-chain aliphatic hydrocarbons in the form of both liquid paraffins and wax deposits, which are well-known to be the primary products evolved from the pyrolysis of polyolefins. The addition of ?-alumina catalyst significantly affects both the distribution and the quality of the pyrolytic products (char, bio-oils, and gas). Under catalytic co-pyrolysis conditions, a marked reduction in the yield of bio-liquid is observed, compensated by a remarkable improvement in its quality, particularly in terms of the formation of light mono-aromatics and a marked decrease in the total amount of the oxygenated compounds. On the downside, however, a significant increase in the production of polycyclic aromatic hydrocarbons (PAHs) is detected. Remarkable benefits are also detected by increasing the co-pyrolysis temperature to 600 °C, particularly in terms of content of oxygenated compounds in the bio-oils, as well as in terms of PAHs and water formation, which decreased considerably. Altogether, preliminary findings of this study suggest that further research efforts are required in order to improve the process performance, for example by optimizing the operating conditions as well as the physicochemical properties of catalysts.